Study on Personality Disorder in a Nigerian Prison Community - Solomon, Enyidah Nonyenim (Highlights on Medicine and Medical Research Vol. 1, 2021)
Background: Personality disorders have since the 19th century been known and established as psychiatric diagnosis, yet very few epidemiological studies have been done. Absence of information about this disorder in the prisons led to the assessment of its prevalence in Agodi prisons in Nigeria. Objective: To determine the prevalence of personality disorder in a prison community in Nigeria. Methods: A total of 213 inmates who met the study criteria were interviewed, using (IPDE) International Personality Disorder Examination, a semi structured questionnaire modified to conform to DSM 111-R and ICD-10 classifications. Using the Statistical Package for Social Sciences (SPSS/PC+), cross tabulation of the variables was obtained using chi-square and t- test. Results: The results showed that at least 31% of prison inmates have personality disorders with antisocial personality disorder being most prevalent. A strong association between criminality and personality disorder was established, and the need for psychiatric services in the prison was recommended. As part of the correctional programs, educational packages should be introduced into Nigerian prisons with focus on vocational and technical education.